Human papilloma virus genotype diversity of anal infection among trans (male to female transvestites, transsexuals or transgender) sex workers in Argentina - Dos Ramos Farías, María Sol (2011)
Fil: dos Ramos Farías, María Sol. Universidad de Buenos Aires. Facultad de Medicina. Departamento de Microbiología, Parasitología e Inmunología. Centro Nacional de Referencia para el Sida; Argentina.